Characterization of Highbush Blueberry (Vaccinium corymbosum L.) Anthocyanin Biosynthesis Related MYBs and Functional Analysis of VcMYB Gene - Yongyan Zhang; Dingquan Huang; Bin Wang; Xuelian Yang; Huan Wu; Pengyan Qu; Li Yan; Tao Li; Chunzhen Cheng; Dongliang Qiu (Current Issues in Molecular Biology, 2023)
As one of the most important transcription factors regulating plant anthocyanin biosynthesis, MYB has attracted great attentions. In this study, we identified fifteen candidate anthocyanin biosynthesis related MYB (ABRM) proteins, including twelve R2R3-MYBs and three 1R-MYBs, from highbush blueberry. The subcellular localization prediction results showed that, with the exception of VcRVE8 (localized in chloroplast and nucleus), all of the blueberry ABRMs were nucleus-localized. The gene structure analysis revealed that the exon numbers of the blueberry ABRM genes varied greatly, ranging between one and eight. There are many light-responsive, phytohormone-responsive, abiotic stress-responsive and plant growth and development related cis-acting elements in the promoters of the blueberry ABRM genes. It is noteworthy that almost all of their promoters contain light-, ABA- and MeJA-responsive elements, which is consistent with the well-established results that anthocyanin accumulation and the expression of MYBs are influenced significantly by many factors, such as light, ABA and JA. The gene expression analysis revealed that VcMYB, VcMYB6, VcMYB23, VcMYBL2 and VcPH4 are expressed abundantly in blueberry fruits, and VcMYB is expressed the highest in the red, purple and blue fruits among all blueberry ABRMs. VcMYB shared high similarity with functionally proven ABRMs from many other plant species. The gene cloning results showed that VcMYB had three variable transcripts, but only the transient overexpression of VcMYB-1 promoted anthocyanin accumulation in the green fruits. Our study can provide a basis for future research on the anthocyanin biosynthesis related MYBs in blueberry.